Polydopamine-Based Biomaterials in Orthopedic Therapeutics: Properties, Applications, and Future Perspectives - Zhang M; Mi M; Hu Z; Li L; Chen Z; Gao X; Liu D; Xu B; Liu Y (Dove Medical Press, 2024)
Min Zhang,1- 3,* Man Mi,1,2,4,* Zilong Hu,3,4,* Lixian Li,3,4 Zhiping Chen,1- 3 Xiang Gao,5 Di Liu,3,4 Bilian Xu,3 Yanzhi Liu1- 3 1Zhanjiang Key Laboratory of Orthopaedic Technology and Trauma Treatment, Zhanjiang Central Hospital, Guangdong Medical University, Zhanjiang, 524037, People's Republic of China; 2Key Laboratory of Traditional Chinese Medicine for the Prevention and Treatment of Infectious Diseases, Guangdong Provincial Administration of Traditional Chinese Medicine (Central People's Hospital of Zhanjiang), Zhanjiang, 524037, People's Republic of China; 3Marine Medical Research Institute of Zhanjiang, School of Ocean and Tropical Medicine, Guangdong Medical University, Zhanjiang, 524023, People's Republic of China; 4Guangdong Provincial Key Laboratory for Research and Development of Natural Drug, School of Pharmacy, Guangdong Medical University, Zhanjiang, 524023, People's Republic of China; 5Stem Cell Research and Cellular Therapy Center, The Affiliated Hospital of Guangdong Medical University, Zhanjiang, Guangdong, 524001, People's Republic of China*These authors contributed equally to this workCorrespondence: Bilian Xu, Marine Medical Research Institute of Zhanjiang, School of Marine and Tropical Medicine, Guangdong Medical University, Zhanjiang, 524023, People's Republic of China, Tel +86-0759-2388588, Email 124879846@qq.com Yanzhi Liu, Zhanjiang Key Laboratory of Orthopaedic Technology and Trauma Treatment, Zhanjiang Central Hospital, Guangdong Medical University, Zhanjiang, 524037, People's Republic of China, Tel +86-0759-3157875, Email liuyanzhi02@163.comAbstract: Polydopamine is a versatile and modifiable polymer, known for its excellent biocompatibility and adhesiveness. It can also be engineered into a variety of nanoparticles and biomaterials for drug delivery, functional modification, making it an excellent choice to enhance the prevention and treatment of orthopedic diseases. Currently, the application of polydopamine biomaterials in orthopedic disease prevention and treatment is in its early stages, despite some initial achievements. This article aims to review these applications to encourage further development of polydopamine for orthopedic therapeutic needs. We detail the properties of polydopamine and its biomaterial types, highlighting its superior performance in functional modification on nanoparticles and materials. Additionally, we also explore the challenges and future prospects in developing optimal polydopamine biomaterials for clinical use in orthopedic disease prevention and treatment.Keywords: polydopamine, biomaterials, nanoparticles, bone, orthopaedics